Physico-chemical assessment of water bodies and Socio-economic analysis from the coastal belt of Chittagong - Sumon Ganguli; Shahidul Islam; Joydeb Garai (Research Centre of Inorganic Materials and Complexs, 2018)
The coastal zone of Chittagong is receiving waste and industrial effluents owing to the industrialization and population growth. The physico-chemical parameters pH, temperature, dissolved oxygen, total dissolved solids, salinity of water bodies near the coastal belt of Chittagong provides valuable information on the quality of water. From the coastal belt of Chittagong, six areas (Banskhali, Anowara, Bandar, Sagorica, Vatiary and Kumira) were selected and studied during March-April 2016. The researcher revealed the water bodies was still conducive since most of the physico-chemical parameters investigated fell within the tolerable limits. Moreover, present socio-economic status was also investigated through the coastal belt of Chittagong.